2009
DOI: 10.1029/2008wr006802
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting discrepancies between discharge and precipitation in high‐altitude area of Chile's Norte Chico region (26–32°S)

Abstract: [1] The water resources of high-altitude areas of Chile's semiarid Norte Chico region (26-32°S) are studied using surface hydrological observations (from 59 rain gauges and 38 hydrological stations), remotely sensed data, and output from atmospheric prediction models. At high elevations, the observed discharge is very high in comparison with precipitation. Runoff coefficients exceed 100% in many of the highest watersheds. A glacier inventory performed with aerial photographs and ASTER images was combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
147
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(168 citation statements)
references
References 54 publications
6
147
1
7
Order By: Relevance
“…As a result, melting of the seasonal snowpack is the major component of the water balance at the regional scale, as shown by Favier et al (2009).…”
Section: Other Hydrological Contributorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, melting of the seasonal snowpack is the major component of the water balance at the regional scale, as shown by Favier et al (2009).…”
Section: Other Hydrological Contributorsmentioning
confidence: 99%
“…Glaciers are often perceived as important water reservoirs in the region, but no quantitative study allows such a statement. Favier et al (2009) showed that, at the regional scale, the main water source is the seasonal snowpack. However, the authors pointed out the fact that glacier contribution needs to be further addressed, because few data were available in high-altitude catchments where glaciers exist.…”
Section: Introductionmentioning
confidence: 99%
“…level, however, the westerly flow is no longer blocked by the Andes but rather forced to ascend, resulting in pre-frontal precipitation enhancement over the subtropical Andes as far north as 30 • S (Barret et al, 2009;Viale and Norte, 2009). Indeed, the few high-altitude records suggest that orographic air uplift produces 2-3 times more annual precipitation up in the Andes relative to the coastal values at the same latitudes (Falvey and Garreaud, 2007;Favier et al, 2008).…”
Section: Synoptic-scale Systemsmentioning
confidence: 99%
“…It has an important orographic influence (Favier, Falvey, Rabatel, Pradeiro, & Lopez, 2009) with a Mediterranean rainfall regime and precipitation occurs predominantly in winter months, during the passage of frontal systems from the southern Pacific (Falvey & Garreaud, 2007). The interannual variability of precipitation is strongly influenced by the El Niño Southern Oscillation, with higher than average amounts during the warm phase (Rutllant & Fuenzalida, 1991).…”
Section: Study Sitementioning
confidence: 99%